Thin-Film Deposition for ZnO-Based Semiconductors: Advantages, Challenges, and Future Directions - Haque, Md Najmul; Khan, Md Yakub Ali (Methods in Science and Technology Studies, 2025)
This research dives into the field of thin film deposition, with a particular emphasis on its application in ZnO-based semiconductors. The examination tries to illustrate the array of benefits, intricate challenges, and bright prospects inherent in this field through an in-depth case study. Notably, the work emphasizes the benefits of thin film deposition techniques in ZnO-based semiconductor production, such as precise control over film thickness, improved material use, and the ability to modify electrical properties. It does, how-ever, recognize the difficulties in assuring uniformity and quality control in deposition, dealing with complex deposition processes, addressing interface effects to maximize device performance, and navigating material compatibility constraints. In terms of the future, the study sees significant potential in the development of advanced materials to augment ZnO-based semiconductor functionalities, the incorporation of nanotechnology to boost performance, and the emergence of novel monitoring strategies for real-time quality assurance during deposition. Sustainable deposition methods are also being considered considering environmental concerns. The study continues by emphasizing the revolutionary significance of ZnO-based semiconductors in many applications and emphasizing the importance of interdisciplinary collaboration to unlock the full spectrum of benefits and overcome hurdles in this dynamic field. This research provides a comprehensive look at the complex domain of thin film deposition in ZnO-based semiconductor environments, shedding light on its potential to transform technological landscapes and inspire creative solutions.